The quest for Jewish belief and identity in the graphic novel - Tabachnick, Stephen Ely (Tuscaloosa : The University of Alabama Press, 2014)
"Many Jewish artists and writers contributed to the creation of popular comics and graphic novels, and in The Quest for Jewish Belief and Identity in the Graphic Novel, Stephen E. Tabachnick takes readers on an engaging tour of graphic novels that explore themes of Jewish identity and belief. The creators of Superman (Jerry Siegel and Joe Shuster), Batman (Bob Kane and Bill Finger), and the Marvel superheroes (Stan Lee and Jack Kirby), were Jewish, as was the founding editor of Mad magazine (Harvey Kurtzman). They often adapted Jewish folktales (like the Golem) or religious stories (such as the origin of Moses) for their comics, depicting characters wrestling with supernatural people and events. Likewise, some of the most significant graphic novels by Jews or about Jewish subject matter deal with questions of religious belief and Jewish identity. Their characters wrestle with belief--or nonbelief--in God, as well as with their own relationship to the Jews, the historical role of the Jewish people, the politics of Israel, and other issues related to Jewish identity. In The Quest for Jewish Belief and Identity in the Graphic Novel, Stephen E. Tabachnick delves into the vivid kaleidoscope of Jewish beliefs and identities, ranging from Orthodox belief to complete atheism, and a spectrum of feelings about identification with other Jews. He explores graphic novels at the highest echelon of the genre by more than thirty artists and writers, among them Harvey Pekar (American Splendor), Will Eisner (A Contract with God), Joann Sfar (The Rabbi's Cat), Miriam Katin (We Are On Our Own), Art Spiegelman (Maus), J.T. Waldman (Megillat Esther), Aline Kominsky Crumb (Need More Love), James Sturm (The Golem's Mighty Swing), Leela Corman (Unterzakhn), Ari Folman and David Polonsky (Waltz with Bashir), David Mairowitz and Robert Crumb's biography of Kafka, and many more. He also examines the work of a select few non-Jewish artists, such as Robert Crumb and Basil Wolverton, both of whom have created graphic adaptations of parts of the Hebrew Bible. Among the topics he discusses are graphic novel adaptations of the Bible; the Holocaust graphic novel; graphic novels about the Jews in Eastern and Western Europe and Africa, and the American Jewish immigrant experience; graphic novels about the lives of Jewish women; the Israel-centered graphic novel; and the Orthodox graphic novel. The book concludes with an extensive bibliography"--Provided by publisher.
Adaptations of the Bible -- Religion and identity in Art Spiegelman's Maus -- The holocaust graphic novel -- The Jewish experience in Europe and beyond -- The American immigrant experience -- Some female American Jewish creators -- Identity and belief in the Israel-centered graphic novel -- The orthodox graphic novel.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 28, 2019).
Master record variable field(s) change: 082
Keywords: Comic books, strips, etc. -- Religious aspects; Judaism and literature; Graphic novels; Jews in literature; Holocaust, Jewish (1939-1945), in literature; Jewish literature -- History and criticism; Jews -- Identity; ART -- Techniques -- Drawing; Comic books, strips, etc. -- Religious aspects; Graphic novels; Holocaust, Jewish (1939-1945) in literature; Jewish literature; Jews -- Identity; Jews in literature; Judaism and literature; Electronic books; Criticism, interpretation, etc